2020
DOI: 10.1111/josh.12933
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Knowledge and Adolescent Substance Use Outcomes

Abstract: BACKGROUND Whether parental permission of alcohol and other drug use in a home environment is protective against substance‐related negative outcomes remains controversial. We investigated substance use at home, with or without parental knowledge, and its association with substance‐related consequences. METHODS The sample consisted of 21,207 U.S. students in the 6th to 12th grades surveyed between 2009 and 2017. Substance use patterns and rates of negative outcomes were analyzed by comparing groups of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…While gender differences were not observed in this study, a significant interaction effect was found for support by age group in three of four outcomes, favoring older participants. It has been well established that parental monitoring and parental support are protective factors against substance use outcomes among teens and adolescents, [ 1 3 ] and our study arrived at those conclusions as well. However, this study also found that parental support is an even stronger protective factor against substance use for older adolescents than it is for younger adolescents.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…While gender differences were not observed in this study, a significant interaction effect was found for support by age group in three of four outcomes, favoring older participants. It has been well established that parental monitoring and parental support are protective factors against substance use outcomes among teens and adolescents, [ 1 3 ] and our study arrived at those conclusions as well. However, this study also found that parental support is an even stronger protective factor against substance use for older adolescents than it is for younger adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings demonstrate that the protective effect of parental support on adolescent experimentation with tobacco and alcohol is even greater as they move into high school, a period associated with more independence and opportunities to participate in risk behavior [ 56 ]. While parental monitoring has long been regarded as an important protective factor for adolescent substance use, [ 1 , 10 ] our observation indicates that parental support may grow in importance in preventing substance use among this population. The importance of parental support as children age may be an important aspect to investigate in future studies.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations